COVID-19 infection prevention and control management during hyperbaric oxygen therapy: a best practice implementation project - Hájek, Michal; Chmelař, Dittmar; Rozložník, Miroslav; Lochmanová, Alexandra; Tlapák, Jakub; Vrbová, Tereza; Klugar, Miloslav; Klugarová, Jitka (JBI evidence implementation, 2023)
OBJECTIVE: This implementation project compared standard operating procedures, accepted preventive measures, and disinfection procedures between the initial stage of the COVID-19 pandemic (first wave: March 15 to May 31, 2020) and the later stages of the pandemic (second and third waves: September 1, 2020 to January 31, 2021). INTRODUCTION: This project sought to improve compliance with international evidence-based guidelines and clinical standards for the prevention and control of COVID-19 infection during hyperbaric oxygen therapy taking into account the conditions of the local hospital. METHODS: Guided by the JBI evidence implementation framework, seven evidence-based audit criteria were developed for the prevention and control of COVID-19 infection during hyperbaric oxygen therapy. A questionnaire was used to measure compliance in baseline and follow-up audits. RESULTS: Differences between the baseline and follow-up audits were noted for criteria 6 and 7. Criterion 6 increased from 0% to 100% as the hyperbaric facility was equipped with certified ultraviolet-C radiation for air disinfection during the later period, but this equipment was not available in the initial period of the pandemic. Criterion 7 dropped from 100% in the baseline audit to 0% in the follow-up audit because of a significant increase in the operational burden of the treatment capacity of the facility, which made it impossible to comply with the recommended distancing between patients. CONCLUSIONS: Differences were found in preventive measures, disinfection procedures, work organization, and approach to care strategy. The project objectives were met and the implementation strategies proved effective. Larger sample sizes would need be needed to confirm the reproducibility of the results.
Keywords: nemocnice; reprodukovatelnost výsledků; pandemie; COVID-19; Hyperbaric Oxygenation; Pandemics; Humans; Hospitals; lidé; Reproducibility of Results; hyperbarická oxygenace